PERHITUNGAN CADANGAN NIKEL LATERIT MENGGUNAKAN METODE INVERSE DISTANCE WEIGHTING - Muh. Adib Hadriawan; Rafiuddin; Syamsuddin (Fakultas Teknik UPRI, 2026)
This research aims to analyze the effect of holding time in the Post Weld Heat Treatment (PWHT) process on the mechanical properties of ST42 steel that has undergone welding using the Shielded Metal Arc Welding (SMAW) method. The main focus of the study is the correlation between variations in heat holding time at a certain temperature and changes in hardness and toughness.The method used is an experiment with variations in holding time, followed by rapid cooling to maintain microstructural homogeneity. Hardness testing is conducted using Vickers or Rockwell methods, while toughness is analyzed through bending/impact tests depending on the appropriate method. The microstructure is examined to check for changes in the fractions of ferrite and pearlite, as well as grain size influenced by heat retention.In conclusion, the holding time during PWHT has a significant effect on the hardness and toughness of ST-42 steel. Adjusting the duration of the heat hold can be used as a control variable to optimize the mechanical properties of the weld, balancing strength and crackresistance according to the needs of engineering applications.